Equaliberty : political essays - Balibar, Étienne, 1942- (John Hope Franklin Center Book., 2014)
First published in French in 2010, Equaliberty brings together essays by Étienne Balibar, one of the preeminent political theorists of our time. The book is organized around equaliberty, a term coined by Balibar to connote the tension between the two ideals of modern democracy: equality (social rights and political representation) and liberty (the freedom citizens have to contest the social contract). He finds the tension between these different kinds of rights to be ingrained in the constitution of the modern nation-state and the contemporary welfare state. At the same time, he seeks to keep rights discourse open, eschewing natural entitlements in favor of a deterritorialized citizenship that could be expanded and invented anew in the age of globalization. Deeply engaged with other thinkers, including Arendt, Rancière, and Laclau, he posits a theory of the polity based on social relations. In Equaliberty Balibar brings both the continental and analytic philosophical traditions to bear on the conflicted relations between humanity and citizenship.